Applicability of an in vitro gastrointestinal digestion method to evaluation of toxic elements bioaccessibility from algae for human consumption. Issue 8 (18th April 2018) - Desideri, Donatella; Roselli, Carla; Feduzi, Laura; Ugolini, Lucia; Meli, Maria Assunta
ABSTRACT: This study aimed to investigate the bioaccessibility of toxic elements, including aluminum (Al), arsenic (As), nickel (Ni), cadmium (Cd), and lead (Pb) in five commercial algae consumed by humans in Italy. The degree of bioaccessibility of these elements may have important implications for human health. Simulation of gastrointestinal tract (GIT) digestion was divided into three stages through use of synthetic saliva, gastric, and bile–pancreas solutions. After pre-treatment with a saliva solution, seaweed samples underwent one of the following treatments: (1) simulated gastric digestion only or (2) simulated complete GIT digestion (gastric digestion followed by bile-pancreas digestion). The bioaccessibility of these toxic elements ranged from approximately 5% to 73% and from 4% to 77% in gastric and GIT digestion, respectively. The bioaccessibility of Al and Pb is poor (5–15%), As and Ni were fairly (40–55%), while Cd displayed a high bioaccessibility. No significant differences in toxic elements mobility was found between samples that only underwent gastric digestion compared to those that underwent a complete GIT digestion.